98 ACUTE GROWTH HORMONE AND TESTOSTERONE CHANGES FOLLOWING TRAUMATIC BRAIN INJURY. (1st January 2006) - Chefteyan, M.; Christenson, P.; Dusick, J. R.; Cohan, P.; Kelly, D. F.
Abstract : Introduction: During traumatic brain injury (TBI) the proper functioning of the hypothalamic-pituitary-adrenal (HPA) axis is an essential component of the neuroendocrine stress response. Growth hormone (GH) and testosterone (via the luteinizing hormone-testosterone axis) are two hormones under the influence of the HPA axis. Given the critical role that GH plays in body growth and metabolism and testosterone's important anabolic properties, this study aims to describe serum GH and testosterone levels in the acute period following TBI and to examine if differences in serum GH and testosterone levels exist between TBI patients with varying Glasgow Coma Scale (GCS) scores, Injury Severity Scores (ISS), and blood pressure (BP) values. Methods: Serum GH and testosterone measurements were obtained from 97 patients during the first 11 days following TBI. Injury severity characteristics such as GCS, ISS and BP values were collected for each patient. Results: During the acute period following TBI, GH levels initially decrease and then increase ( p = .0004). Testosterone follows the same pattern ( p < .0001). The comparison of mean GH and testosterone values within 24 hours of injury and over the 11 days following TBI between patients with different GCS, ISS, and BP values demonstrates that a statistically significant difference of serum hormone levels does not exist when patients are stratified using these parameters. Conclusions: These preliminary data suggest that both GH and testosterone initially decrease and then increase in the acute period following TBI. Although there is an increase in GH and testosterone toward the end of the observation period, for at least the first week post-injury, somatotroph and gonadotroph suppression occurs in the majority of patients. The clinical importance of this suppressed hormonal function remains to be determined. Additionally, differences in injury severity measurements do not correlate with different patterns of GH and testosterone levels.